EDUCATION IN THE PERIOD OF COVID-19 PANDEMIC. POSITIVE AND NEGATIVE ASPECTS OF DISTANCE EDUCATION - Kushmatova Dildora Ergashevna; Ravshanov Sherxon Ulug’bekovich; Khaydarov Odilkhon Lazizovich (Scholar Express Journals, 2023)
The COVID-19 pandemic has had an impact on all aspects of our lives, including education. The quarantine measures applied by multiple countries of the world affected different education types and systems. In most countries a total transition to online learning has taken place. Distant learning is a form of education in which the student’s location is remote from the teacher and educational resources, the teaching is carried out with the help of computer technologies
Keywords: Pandemic; education; COVID-19